Five new species of the Ghost Spider genus Anyphaenoides Berland from Colombia (Araneae: Anyphaenidae: Anyphaeninae) - Martinez, Leonel; Brescovit, Antonio D.; Martinez, Neis (Zootaxa, 2018)
Five new species of the ghost spider genus Anyphaenoides Berland from Colombia are described and illustrated: A. sierraensis sp. nov. (based on male and female) from Magdalena department, A. caribensis sp. nov. (male and female) from Atlántico department, A. foreroi sp. nov. (male) from Vaupes department, A. hilli sp. nov. (male) from Putumayo department and A. enigmaticus sp. nov. (male and female) from Santander department.